Association between polymorphism of dopamine D2 receptor genes and therapeutic effect of domperidone in functional dyspepsia - Xiang, Zun; Ma, Han; Mou, Yun; Xu, Cheng-fu (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Functional dyspepsia (FD) is a common gastrointestinal disease, for which domperidone is one of the most commonly used drugs. This study aimed to investigate the potential causes of the varying therapeutic effects of domperidone among FD patients. Materials and Methods: The effects of domperidone therapy in patients with FD were evaluated using a clinical symptom score combined with real-time ultrasonography examination of antral motor index. Single nucleotide polymorphism (SNP) of the dopamine D2 receptor genes 141C Ins/Del, A-241G, and TaqI, were analyzed by ligase detection reaction. Results: The results of real-time ultrasonography correlated with clinical symptom scores. Single nucleotide polymorphism analysis of dopamine D2 receptor TaqI gene showed that the genotype frequencies of “C/C”, “C/T”, and “T/T” in the effective group were 51.35%, 31.08%, and 17.57%, respectively; the allele frequencies were 66.89% and 33.11%. In the ineffective group, the genotype frequencies of “C/C”, “C/T”, and “T/T” were 17.81%, 52.05%, and 30.14%, respectively; and the allele frequencies were 43.84% and 56.16%. The difference was statistically different between the two groups (p<0.01). Conclusion: Clinical symptom scores combined with real-time ultrasonography is effective in evaluating the therapeutic effect of domperidone in patients with functional dyspepsia. The therapeutic effect of domperidone in these patients was associated with polymorphism of dopamine D2 receptor TaqI gene.